Model Pembelajaran The Learning Cell untuk Kepercayaan Diri dan Kemampuan Komunikasi Siswa di MIS Darul Ihsan - Humairo (putrapublisher.org, 2024)
Learning is essentially to develop students' abilities both academically and non-academicly. Apart from achieving learning objectives based on basic competencies and indicators, the learning process also needs to develop aspects of students' personalities. Teachers must become facilitators for students to become more skilled in various fields. Self-development that teachers can improve and internalize through learning activities is self-confidence and communication skills. Students will need these two things as preparation to be ready and brave enough to express their aspirations in society. The learning cell learning model is a learning method that provides opportunities for students to actively interact with fellow students and encourages students to get used to appearing in front of other friends. Through this activity, student activity is increased, indirectly, students who have a turn to ask questions and answer are trained to be confident in conveying, and their verbal communication skills are also trained.